ANALISIS HUKUM PELAKSANAAN PEMBIAYAAN TALANGAN UMROH BERDASARKAN AKAD IJARAH DALAM PERJANJIAN PEMBIAYAAN UMROH DI PEKANBARU - Firmansyah, Doni; Jayakusuma, Zulfikar; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The presence of one of the financing institutions, namely consumer finance companies in Indonesia today, especially in the city of Pekanbaru is inseparable from the problem of secondary needs that must be met by every member of the community. This consumer finance company is very helpful to ease the burden of consumers when compared to business transactions in the form of cash or cash. With the interest and needs of the community to perform Umrah but have limited funds, this Umrah bailout product is one solution. This Umrah bailout product has a great opportunity because the population of Indonesia is a majority of Muslims and supported by optimal marketing.PT Bess Syariah is one of the financial institutions in the city of Pekanbaru.This type of research can be classified in the type sociological juridical research. The research was conducted at PT Bess Syariah in pekanbaru city. Sociological law research uses primary data and secondary data,while population and sample are the parties related to problem studied in this research. Technique of collecting data in this research by interview and literature study. From the results of the problem research there are three points that can be concluded first. The regulation on umrah financing based on the ijarah principle is regulated based on the DSN-MUI no. 9 fatwa on ijarah financing, but there are still differences of opinion among the ulama regarding the halal law. issued PMA No. 8 of 2018 concerning the implementation of Umrah pilgrimage services which had banned the financing of the bailout. Second, the Umrah bailout financing carried out by Pt. Bess Syariah does not fully implement sharia principles based on the provisions in the DSN_MUI No 19 fatwa regarding ijarah financing as evidenced by the use of collateral objects which are not regulated in the MUI fatwa. Third, the parties who are still committing violations can be subject to sanctions contained in article 41 paragraph (1) PMA No. 8 of 2018, which says "PPIU that violates the provisions referred to in Article 12, is subject to written warning sanctions", in paragraph (2) " PPIU which repeats violations as referred to in paragraph (1) shall be subject to sanctions for suspension of operating licenses no later than 2 (two) years ".Keywords: Financing, Ijarah